The effect of family ownership and generation on financial literacy - Antonio Molina-García; Belen Florido-Ruiz; Marta Campos Valenzuela; Julio Diéguez-Soto (Small Business International Review)
The purpose of this article is to study the effect of family ownership and family generation on financial literacy. To do that, we have analysed a sample of 195 Spanish family businesses, reaching the conclusion that the level of family ownership exerts a negative influence on financial literacy. On the other hand, as family generations advance, financial literacy is favoured. This study benefits professionals and entrepreneurs, since they could, through a series of guidelines, improve financial literacy and, with it, the viability of their respective firms